2001
DOI: 10.4037/ajcc2001.10.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nurses' knowledge of arterial pressure monitoring

Abstract: BACKGROUND: Direct monitoring of arterial blood pressure provides continuous, real-time information about patients' physiological status. Critical care nurses set up and maintain monitoring systems and use the obtained data to guide clinical decisions. Inaccurate measurements may lead to misdiagnosis and mismanagement. PURPOSE: To describe critical care nurses' knowledge in 3 content areas related to direct monitoring of arterial blood pressure: physiology, technical aspects, and waveform and data interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…The results of this study showed that competence in nursing in the ICCU involves both clinical and professional competence. The clinical aspect of competence in nursing also emerged in the findings of other studies that had examined intensive care nursing ( 7 , 19 , 20 ). Aari et al (2008) considered nursing interventions, basic care, understanding humans’ physical and psychological functions, and monitoring patients as part of clinical competence in intensive care nursing ( 7 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The results of this study showed that competence in nursing in the ICCU involves both clinical and professional competence. The clinical aspect of competence in nursing also emerged in the findings of other studies that had examined intensive care nursing ( 7 , 19 , 20 ). Aari et al (2008) considered nursing interventions, basic care, understanding humans’ physical and psychological functions, and monitoring patients as part of clinical competence in intensive care nursing ( 7 ).…”
Section: Discussionmentioning
confidence: 83%
“…The findings of this study showed that recognizing the critical conditions of patients and performing emergency care are part of clinical competence. Detecting abnormal conditions in critical care nursing also is part of clinical competence in nursing ( 19 , 20 ). The results of the study showed that clinical competence is partly about recognizing patients’ needs and then providing nursing care according to those needs.…”
Section: Discussionmentioning
confidence: 99%
“…These should include understanding the anatomical and physiological principles. While nurses are competent with practice skills, they often lack understanding of the underpinning principles of many practical nursing skills (Gillepsie and Curzio, 1998; Beitz et al ., 1999; McGhee and Woods, 2001; Hall and Sutton, 2002). Although, traditionally nurses were viewed as caring to the point of self‐sacrifice, which instead of knowledge required utter devotion (Dalley, 1988), nursing care cannot be holistic if the underpinning principles of health and illness are not understood (Clarke, 1995; Edwards, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It was often remarked that while nurses were often competent with practical skills, they might lack understanding of the underpinning principles of care (Gillepsie & Curzio 1998, Beitz et al. 1999, McGhee & Woods 2001, Hall & Sutton 2002). Although it was suggested that traditionally nurses prioritized ‘utter devotion’ over knowledge (Dalley 1988) contemporary evidence‐based approaches require a sound knowledge base (Clarke 1995, Edwards 2001).…”
Section: Discussionmentioning
confidence: 99%